Akuntabilitas Pengelolaan Dana Desa Kabupaten Bantul - M Sulkhanul Umam; Vidya Vitta Adhivinna; Mayka Wulandari (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2023)
This study was conducted to examine the effect of accessibility of financial statements, internal control system, organizational commitment, competence of village officials, and the role of village officials on village fund management accountability. This research was conducted in five Kapanewon, Bantul Regency, totaling 29 Kalurahan. The research sample amounted to 101 respondents where the sampling technique used purposive sampling. The research method used is quantitative research with technical data analysis in the form of multiple linear regression where the hypothesis test uses a significance level of = 0.05 with the help of SPSS version 26.0. The results of this study indicate that the accessibility of financial reports, internal control systems, organizational commitment, competence of village officials, and the role of village officials affect the accountability of village fund management.